Collaborative Mentorship for Transformative Teachers: Catalyzing Best Practice Publication in Urban Education - Ngabiyanto, Ngabiyanto; Isnarto, Isnarto; Utomo, Asep Purwo Yudi; Yanitama, Arka; Kesuma, Rossi Galih; Widhiyanto, Riyadi; Oktaviyanti, Sefti Dwi; Irfanti, Dwi (Journal of Community Empowerment, 2024)
The study explores the impact of collaborative mentoring on transformative teachers' ability to publish best practices in urban education in Semarang City, Indonesia. Besides the important role of transformative teachers in improving the quality of education, the best practices were underexposed and adequately documented. Using the Participatory Community Appraisal (PCA) approach, the study involved 24 transformative teachers in a structured mentoring program focused on identifying, documenting, and publishing best practices. The program includes intensive workshops, ongoing online support, and peer collaboration. The results showed a transformative teachers can articulate and disseminate innovative practices, with 80% of participants successfully publishing the work on various platforms. The study concludes that collaborative mentoring catalyzes the publication of best practices, thereby increasing knowledge sharing among educators and potentially improving the quality of urban education. This research contributes to the growing literature on teacher professional development and highlights the importance of structured support in promoting the spread of educational innovation.